Contribution of Co-Skewness and Co-Kurtosis of the Higher Moment CAPM for Finding the Technical Efficiency - Hasan, Md. Zobaer; Kamil, Anton Abdulbasah (Hindawi Publishing Corporation, 2014)
The objective of this paper is to present the technical efficiency of individual companies and their respective groups of Bangladesh stock market (i.e., Dhaka Stock Exchange, DSE) by using two risk factors (co-skewness and co-kurtosis) as the additional input variables in the Stochastic Frontier Analysis (SFA). The co-skewness and co-kurtosis are derived from the HigherMoment Capital Asset Pricing Model (H-CAPM). To investigate the contribution of these two factors, two types of technical efficiency are derived: (1) technical efficiency with considering co-skewness and co-kurtosis (WSK) and (2) technical efficiency without considering coskewness and co-kurtosis (WOSK). By comparing these two types of technical efficiency, it is noticed that the technical efficiency ofWSK is higher than the technical efficiency ofWOSK for the individual companies and their respective groups. As per available literature in the context Bangladesh stockmarket, no study has been conducted thus far to measure technical efficiency of companies and their respective groups by using the risk factors which are derived from the H-CAPM. In this research, the link between HCAPM and SFA is established for measuring technical efficiency and it is believed that the findings of this study may be applied to other emerging stock markets.